Bioassay of cyanoacrylate tissue adhesives used for intraperitoneal mesh fixation. Issue 2 (27th October 2015) - Bellón, Juan M.; Fernández‐Gutiérrez, Mar; Rodríguez, Marta; Sotomayor, Sandra; Pérez‐Köhler, Bárbara; Kuhnhardt, Andree; Pascual, Gemma; San Román, Julio
Abstract: Aims: This study examines the intraperitoneal behavior of two cyanoacrylate tissue adhesives: Ifabond ® and a new, non‐marketed octyl cyanoacrylate adhesive (OCA) used for the intraperitoneal fixation of a laminar expanded polytetrafluoroethylene (ePTFE) mesh.Material and Methods: In 36 New Zealand White rabbits, 3 × 3 cm ( n = 24) or 1.5 × 3 cm ( n = 12) fragments of ePTFE mesh (Preclude ®, Gore, Flagstaff, USA) were fixed to the parietal peritoneum using OCA or Ifabond ® . Peritoneal fluid was obtained at the time of implant and at 2 weeks postimplant for determination of the cytokines interleukin‐6 (IL‐6) and tumor necrosis factor alpha (TNF‐α). At 14 or 90 days postsurgery, the animals were euthanized and the meshes excised to assess host tissue incorporation, the macrophage response, apoptosis and fixation strength (T‐peel tensiometry).Results: Peritoneal fluid IL‐6 and TNF‐α concentrations were similar in the OCA and Ifabond ® groups. Both adhesives gave rise to adequate mesothelialization of the laminar ePTFE. Macrophage counts were similar for the two study groups, but a significantly increase in macrophage response was observed from 14 to 90 days for Ifabond ® . At 90 days postimplant, apoptotic cell counts was lower for the implants fixed with OCA and a fixation strength was significantly lower for OCA.Conclusions: Despite similar cytokine levels at 2 weeks and similar host tissue incorporation observed for the meshes fixed with the two adhesives, the use of Ifabond ® gave rise to a greater apoptosis rate, although this adhesive provided a stronger fixation bond. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 312–319, 2017.